Cestodes fauna of silvery mole rats (Heliophobius Argentiocinereus Emini) in Morogoro Region, Tanzania (Journal of Ideas in Health, 2024)
Background: Silvery mole rat (Heliophobius Argentiocinereus) is a subterranean rodent widely distributed throughout Sub-Saharan Africa. They have been reported to host several gastrointestinal parasites, however, the status of parasites from these rats in Tanzania has not been widely studied. This study aimed to investigate the prevalence of cestodes parasites in silvery mole rats from the Morogoro region. Methods: A cross-sectional study was conducted in the Mlali and Mji mkuu wards of the Mvomero and Morogoro urban districts in Tanzania, from March to June 2023. Silvery mole rats were collected through manual excavation of their burrows in agri-ecological areas. The captured rats were euthanized using Diethyl Ether and dissected to remove the gastrointestinal tract (GIT). GIT contents were gathered. Adult worms were collected and preserved in 70.0% ethanol. A flotation and aceto-carmine staining techniques were employed to process gastrointestinal contents and adult tapeworms respectively. Both cestode eggs and adult tapeworms were identified based on general morphological features using taxonomic keys. The prevalence of cestodes was computed, and a chi-square test was applied to assess association, a p-value≤ 0.05 was considered significant.Results: One hundred thirty-seven silvery mole rats were collected, adult females 65% (89/137) were dominant among collected rats. One species of gastrointestinal cestode was detected with an overall prevalence of 20.44% (28/137) and identified as Hymenolepis diminuta. A total of 392 adult worms and 1450 eggs per gram (EPG) for H.  diminuta were collected from the gastrointestinal tract. A significant association was shown between cestodes infection with both host age and reproductive category (p< 0.05).Conclusion: This study has established that Hymenolepidae (H. diminuta) is prevalent in silvery mole rats of the Morogoro region, suggesting that this animal could be among the sources of hymenolepiasis disease in the community. Therefore, further studies are needed to investigate cestodes fauna in community members of the respective study area.
Keywords: Hymenolepis diminuta, Prevalence, Morogoro, Silvery Mole Rats, Endoparasites, Tanzania